Aerobic power and supramaximal endurance of competitive figure skaters - Mannix, E. T.; Healy, A.; Farber, M. O. (The Journal of Sports Medicine and Physical Fitness, 1996)
This study was supposed to assess training forms and training responses in competitive figure skaters (M = 3, F = 12). Skaters were formed into two groups, one performing only on-ice training and the other doing on-ice training plus off-ice cycle ergometer training. Measures of peak oxygen consumption, anaerobic threshold, heart rate, supramaximal exercise time, and the lactate response to exercise were taken. It was found that on-ice training did not change any of the measure but the added cycle work did. However, the premises for the conclusions of this study are spurious. What was found is as follows: 1.Specific on-ice training does not show changes in non-specific (cycle) testing parameters. 2.When skaters are asked to also train on a cycle, cycle testing parameters do reflect changes in cycle training status. 3.Any implied benefit from cycle training for on-ice performance is neither warranted nor substantiated in this study. The authors' recommendation of the value of cross-training of this nature for figure skating is an opinion not an objective result of this study. 4.This investigation failed to show any benefit of cycle training for ice-skating performance. Implication: The recommendations of this study's authors are spurious. All that is shown is that how one trains governs the type of training response. Essentially, if an athlete has not trained for cycling and commences to do so, then the physiological measures associated with cycling change (improve). Measures in non-cycling activities most probably will not, and in this case did not, change.